TEACH and repeat: Deliberate practice for teaching. (10th July 2020) - Marcus, Carolyn H; Newman, Lori R; Winn, Ariel S; Antanovich, Kate; Audi, Zeena; Cohen, Amy; Hirsch, Alexander W; Harris, Holly K; Miller, Kelsey A; Michelson, Catherine D
SUMMARY: Background: Deliberate practice facilitates skill mastery. We aimed to create a novel resident‐as‐teacher rotation, leveraging a deliberate practice framework with repeated practice in real‐life teaching settings, with feedback from dedicated faculty member coaches. Methods: A resident‐as‐teacher rotation was designed for 35 Postgraduate Year‐2 (PGY2) paediatric residents. To facilitate deliberate practice, teaching experiences were observed by faculty member coaches and were repeated with different audiences. Participating residents received pre‐rotation, post‐rotation and follow‐up surveys on their confidence and comfort with teaching, supervision and feedback skills. All residents were also surveyed the year before and the year after implementation on their perceptions of their teaching, supervision and feedback skills, and whether the residency provided adequate training on these topics. Results: Survey response rates varied from 40 to 71%. The rotation was highly valued, and deliberate practice was a most valued aspect. Mean scores in comfort and confidence significantly increased from pre‐ to post‐rotation, with these increases sustained months later. Prior to implementation, residents' perceptions of their teaching skills and the adequacy of their training increased incrementally with each postgraduate year. After the inaugural year of the rotation, the PGY2 class rated their teaching skills and training as higher than more experienced residents. Discussion: A novel resident‐as‐teacher rotation successfully incorporated deliberate practice in real‐life settings by repeating teaching activities with feedback from dedicated coaches. The rotation led to sustained increases in residents' confidence in their teaching, supervising and feedback skills, and improved perceptions of their teaching training during residency.